Case Report: Homozygous C677T MTHFR Gene Mutation in Male with Hypogonadism - Rami Salameh; Mumtaheena Miah; Catherine Anastasopoulou (Case Reports in Endocrinology)
We report a 44-year-old male, who was diagnosed with hypogonadotropic hypogonadism after complaining of erectile dysfunction, depression, and fatigue. He was started on testosterone replacement therapy. He persistently complained of fatigue despite increasing the dose of testosterone over two years and having therapeutic testosterone levels. He was found to have homozygous C677T methylenetetrahydrofolate reductase (MTHFR) gene mutation. After treatment with folate and B12, his symptoms resolve completely. MTHFR is a key enzyme in the folate pathway, and it plays an essential role in homocysteine metabolism. Homozygous C677T individuals have decreased activity of MTHFR enzyme with increased homocysteine levels, which is associated with increased risk of thrombosis. An association has been reported between C677T variant and male infertility. Patients identified to have hyperhomocysteinemia should be treated with B-complex vitamin supplements. Our case emphasizes other possible etiologies for fatigue and erectile dysfunction in a male with hypogonadism on testosterone therapy. Also, it shows possible association between MTHFR gene mutation and male hypogonadism.